PENENTUAN KEBUTUHAN NITROGEN TANAMAN JAGUNG (Zea mays L.) PADA BERBAGAI JARAK TANAM DALAM TUMPANGSARI DENGAN KACANG TANAH (Arachis hypogeae L.) DI LAHAN KERING MALUKU TENGAH - Rivaie, Achmad Arivin (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2014)
Most people in Maluku Islands have long used non-rice food consumption, especially tuber crops and maize. The development of diversification of non-rice food consumption certainly needs to be supported by the availability of adaptive crop cultivation technology to climate change. Cropping pattern is one of the appropriate steps for smallholder farmer to increase land productivity. An experiment of maize/peanut intercropping pattern had been conducted to determine optimum Nitrogen (N) rate for maize at different planting spacings in intercropping pattern with peanut in dryland of Makariki Village, Central Maluku. The experiments were arranged in a Split Plot Design with 3 (three) replicates. The main plot was maize spacing, namely: (i) J1 = 80 x 25 cm, 6 rows of maize, 2 rows of peanut, (ii) J2 = 160 x 25 cm, 3 rows of maize, 4 rows of peanut, and (iii) J3 = 240 x 25 cm, 2 rows of maize, 6 rows of peanut. The sub-plot was N rate (kg/ha), namely: (i) N0 = 0-0-0, (ii) N1 = 45-50-60, (iii) N2 = 90-50-60, (iv) N3 = 135-50-60, and (v) N4 = 180-50-60. The results showed that plant height, cob circle and yield of maize grown at different planting spacings in intercropping patterns in Makariki, Central Maluku affected by N fertilizer application. The application of N fertilizer increased growth and yield of maize by following a quadratic pattern. The use of maize spacing of J1 (80 x 25 cm) in intercropping with peanut requires the addition of the optimum N rate of 302 kg urea/ha, which gave the highest maize yield (t/ha) compared with other planting spacings.